Climate change transformations in Nordic agriculture?. (April 2017) - Juhola, Sirkku; Klein, Natacha; Käyhkö, Janina; Schmid Neset, Tina-Simone
Abstract: Climate change is expected to have negative impacts but also to bring potential opportunities for agriculture and crop productivity in the Nordic countries. Little research has been conducted at the farmer level to identify what adaptation measures are being considered or already taken and transformative these are. Based on semi-structured interviews with farmers and extension officers from two of the most fertile agricultural areas of Finland and Sweden, this study examines to what extent Nordic farmers are engaged in transforming their farming systems. The results show that some transformational changes are taking place already but most changes are incremental. Currently, agricultural policies and regulations are perceived as a greater adaptation challenge than climate change. Highlights: Climate change poses risks to Nordic agriculture as well as opportunities. Nordic farmers are taking measures that are transformational. Climate change is currently not considered a major driver for action.